Arte infantil y educación artística - Marín, RICARDO; Bustamante, MARÍA JOSÉ; Casares, LOURDES; Flores, NICOLÁS; García, TERESA; Puentes, MANUEL; Ruiz, MARÍA; Martínez, Virtudes (Arte, Individuo y Sociedad, 2002)
Sin resumen